Effect of angiotensin receptor-neprilysin inhibitor on atrial electrical instability in atrial fibrillation - Zhu, Tianyu; Zhang, Wenchao; Yang, Quan; Wang, Ning; Fu, Yuwei; Li, Yan; Cheng, Guanliang; Wang, Liang; Zhang, Xian; Yao, Hongying; Sun, Xinghe; Chen, Yu; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background and objective Around 33.5 million patients suffered from atrial fibrillation (AF), causing complications and increasing mortality and disability rate. Upstream treatment for AF is getting more popular in clinical practice in recent years. The angiotensin receptor-neprilysin inhibitor (ARNI) is one of the potential treatment options. Our study aimed to investigate the effect of ARNI on atrial electrical instability and structural remodeling in AF. Methods Our research consisted of two parts – a retrospective real-world clinical study and an animal experiment on calmness to verify the retrospective founding. In the retrospective study, we reviewed all patients (n = 110) who had undergone the first AF ablation from 1 August 2018 to 1 March 2022. Patients with ARNI (n = 36) or angiotensin II receptor antagonist (ARB) (n = 35) treatment were enrolled. Their clinical data, ultrasound cardiogram (UCG) and Holter parameters were collected before radiofrequency catheter ablation (RFCA) as baseline and at 24-week follow-up. Univariate and multivariate logistic regression analysis were performed. In the animal experiment, we established an AF model (n = 18) on canines by rapid atrial pacing. After the successful procedure of pacing, all the 15 alive beagles were equally and randomly assigned to three groups (n = 5 each): Control group, ARB group, and ARNI group. UCG was performed before the pacing as baseline. Physiological biopsy, UCG, and electrophysiological study (EPS) were performed at 8-week. Results Clinical data showed that the atrial arrhythmia rate at 24-week was significantly lower in ARNI group compared to ARB group (P < 0.01), and ARNI was independently associated with a lower atrial arrhythmia rate (P < 0.05) at 24-week in multivariate regression logistic analysis. In the animal experiment, ARNI group had a higher atrial electrical stability score and a shorter AF duration in the EPS compared to Control and ARB group (P < 0.05). In the left atrium voltage mapping, ARNI group showed less low voltage and disordered zone compared to Control and ARB group. Compared to Control group, right atrium diameter (RAD), left ventricle end-diastolic volume index (LVEDVI), E/A, and E/E′ were lower in ARNI group (P < 0.05) at the 8-weeks follow-up, while left atrium ejection fraction (LAEF) and left ventricle ejection fraction (LVEF) were higher (P < 0.01). Compared to ARB group, LVEF was higher in ARNI group at the 8-week follow-up (P < 0.05). ARB and ARNI group had a lower ratio of fibrotic lesions in the left atrium tissues compared to Control group (P < 0.01), but no difference was found between the ARB and the ARNI group. Conclusion ARNI could reduce atrial electrical instability in AF in comparison with ARB in both retrospective study and animal experiment.